Preconceito, religiosidade e representações sociais : articulações sobre a esquizofrenia - Moura, Linniker Matheus Soares de (2021)
As for the theme of mental disorders, prejudice is an element that has been systematically reintroduced, and studies show that some disorders suffer more prejudice than others, such as schizophrenia. Thus, studying this phenomenon requires several views and analyzes, mainly on elements that influence this dynamic that encompasses practices, diverse realities and social representations. Studying these representations also allows contact with all this social and psychic dynamics and allows analyzing aspects that interfere in social dynamics, with a view to the social inclusion of people with mental disorders, more specifically schizophrenia. This dissertation will follow the format of articles, theoretical and empirical, in order to treat the proposed theme with a certain scientific depth. Article 1, entitled “Prejudice, Religiosity and Social Representations: theoretical articulations on schizophrenia”, brings a theoretical discussion whose objective is to lead the reader to reflect on the influence of the context in the formation and maintenance of prejudice, as well as in the genesis and development social representations, and questioning the role of religiosity in this dynamic. In this way, we argue that prejudice arises from social dynamics and can be modulated by elements of social reality such as religiosity, a variable that has been shown to be important in international studies on prejudice and that has also been relevant when discussing the relationship between society and people with mental disorders. Article 2, entitled “Schizophrenia and its Social Representations”, aimed to survey and analyze social representations about schizophrenia in a sample of the general population (N = 80; mean age 29.91 years, SD 10.81), finding that it continues to have a strongly negative aspect, focusing on pathologization and symptoms, linked the disorder to stigmatized stereotypes, such as those of dangerousness and aggressiveness. The representation brings the strength of the affective component "fear", in the central nucleus, indicating that the negative view on schizophrenia influences the emotions expressed towards people with this disorder. It was possible to identify that prejudice and social exclusion were presented as important elements of the relationship between society and people with schizophrenia, demonstrating the strength that representations have as modulators of actions and influencers of behavior. Article 3, entitled “Adaptation and validation of the Emotional Expression Scale for the context of schizophrenia”, was subdivided into two studies with the aim of adapting and validating the Emotional Expression Scale proposed by Djiker in his study on the role of emotions in intergroup relationships, finding sufficiently satisfactory evidence of the factorial validity and internal consistency indexes to consider that the scale, consisting of eight items and two factors, is an instrument with good psychometric properties, with two correlated factors (F1: negative emotions of distance - eingenvalue 4.55; explained variance 56.98%; α = 0.89 / F2: negative emotions of distrust - eingenvalue 1.25; explained variance 15.69%; α = 0.82). Article 4, entitled “Emotions, Stereotypes, Rejection of Intimacy in the Face of Schizophrenia and Religious Attitude: A Correlational Study”, aimed to measure the levels of rejection of intimacy, negative stereotypes, negative emotions, religious beliefs about schizophrenia and religiosity in a sample of the general population (N = 281; mean age 30.04; SD 12.50), correlating them in search of explanatory evidence of prejudice. The results indicate that the sample showed a level of religious attitude above the midpoint with an average of 3.28 points (SD = 1.16; median = 3.6). All variables showed significant positive correlations with each other; and mediation analyzes have shown that the relationship between religious attitude and variables that measure prejudice is mediated in a statistically relevant way by religious beliefs about schizophrenia. The results presented in this dissertation not only corroborate the existing literature on prejudice against schizophrenia, but also promote advances, as it proposes new elements for analysis, consider the influence of religious attitude and beliefs as well as present analyzes that allow to verify how the effect of one variable impacts on another as we add mediating variables.